Higher education institutions: students view and anticipation of attrition/ Erica Joanne Reuben and Nur Afiqah Ramlee - Reuben, Erica Joanne; Ramlee, Nur Afiqah (2018)
The main purpose of this study is to identify the reasons of attrition among students in higher education institution and to identify the opinion of the students on how to reduce attrition in higher education institution. The objective of this research is to identify the reasons of attrition among students in higher education institution and to identify the opinion of the students on how to reduce attrition in higher education institution. The study done based on cross-sectional design, it used quantitative method. In order to achieve both objectives, this research used the survey study method, the questionnaire was distributed to find out the responses from the respondents of UiTM Sabah. It was found that attrition in higher education institution happened because of individual factor. The female respondents aged between 18-20 years old which is AM110 students of semester 3 and 5 stated that attrition in UiTM Sabah caused by individual factor. The second objective, the study found that majority of the respondents stated that PTPTN helps to reduce their financial burden and future career were the motivation that they needed to complete their study. Apart from that, they prefer to have a caring lecturer that able to help them to deal with difficulties in their studies. Besides, most of the respondent stated that the attendance of the students to the class should be monitored so that they are more disciplined and afraid to skip class. Despite from that, students in higher education institution also need counselling to help them to have a better understand of themself, situation and also be wise in dividing time. Lastly, the future benefit of these findings were, it is crucial in order to give awareness of the attrition issue towards the government, university lecturers, educators, academician, parents, university students as well as the people at large. Most importantly, by doing more future studies on this problem helps all of the stakeholders to understand the needs of university students as wholly.